Mother and child characteristics at birth and early age leukemia: a case-cohort population-based study, - Rejane de Souza Reis; Neimar de Paula Silva; Marceli de Oliveira Santos; Julio Fernando Pinto Oliveira; Luiz Claudio Santos Thuler; Beatriz de Camargo; Maria S. Pombo-
Abstract Objective: The population-based cancer registries (PBCR) and the Information System on Live Births in Brazil (Sistema de Informações sobre Nascidos Vivos [SINASC]) have information that enables the test for risk factors associated with leukemia at an early age. The aim of this study was to identify maternal and birth characteristics associated with early-age acute leukemia (EAL) in Brazil. Methods: A case-cohort study was performed using secondary dataset information of PBCR and SINASC. The risk association variables were grouped into (i) characteristics of the child at birth and (ii) characteristics of maternal exposure during pregnancy. The case-control ratio was 1:4. Linkage was performed using R software; odds ratio (OR) and 95% confidence interval (CI) were calculated by logistic regression models. Results: EAL was associated with maternal occupational exposure to chemicals (agricultural, chemical, and petrochemical industry; adjOR: 2.18, 95% CI: 1.16-4.10) and with birth defects (adjOR: 3.62, 95% CI: 1.19-11.00). Conclusions: The results of this study, with the identification of EAL risk factors in population-based case-cohort study, strengthen the knowledge and improve databases, contributing to investigations on risk factors associated with childhood leukemia worldwide.